THE EFFECT OF TAPIOCA FLOUR AS A SUBSTITUTION OF WHEAT FLOUR TO THE PHYSICAL PROPERTIES OF WET HERBAL NOODLES - Chelvia Faramudita Dessuara (The University of Lampung, 2015)
The aims of this researchwere to find out the effect of the amount of tapioca flour subtituted inwheat flour on thephysical attributes ofwet herbal noodles. The studywas analyzedwith the completely randomized designwith 4variations of substitutiontapiocawhich are 0%, 10%, 20%, and 30%with 3 repetitions for each treatment. Theresults showthat the higher the substitutionof tapioca flour, the higher thewater content and tensile strength, butthe lower thewater absorption and swell noodles. The average score of each composition in the hedonic test tendsto be on the classification dislike – neutral. Noodles with tapioca flour tend to bemore durable. The analysis ofvariance and Duncan test ( <0,05) show that substitution of tapioca significantly affects moisture content,tensile strength, and the HSI color, but tapioca substitution does not influence the water absorption and swellnoodles.Keywords : Herbalwet noodles, Food quality, Tapioca flour